Land use and cover change significantly enhanced evapotranspiration in the Yellow River Delta from 2000 to 2023 - Ziqi Mai; Zhongen Niu; Ying Zhao; Pan Li; Yi Wang; Yan Lv; Bin Wang; Mengyu Zhang (Journal of Hydrology: Regional Studies)
Study region: Yellow River Delta (YRD), China's youngest wetland ecosystem Study focus: Drastic land use and cover change (LUCC), along with environmental shifts, have significantly affected evapotranspiration (ET) in YRD. However, few studies have examined the spatiotemporal patterns and drivers of ET due to satellite-based data constraints. We used the PT-JPL model and Dalton formula based on high-resolution satellite data to simulate ET from 2000 to 2023 and quantified the relative contributions of LUCC and environmental factors. New hydrological insight for the region: ET in YRD has significantly increased over the past decades, with an annual rise of 2.13 × 10⁻² gigatons of water per year (P < 0.01). LUCC, particularly the expansion of water areas, have been a major driver, contributing 42.90 % to the ET increase. Meanwhile, the conversion of water areas to vegetation areas has offset 13.06 % of this rise. In areas without such changes, environmental factors were the main influence. ET in vegetation areas was mainly influenced by enhanced vegetation index and net radiation, while in water areas, it was affected by runoff and temperature. This research offers insights into water balance mechanisms between vegetation and water areas and thus sustainable water management in the YRD.